Kompetensi Guru Bahasa Indonesia di SMP Negeri Simpang Kosgoro Kabupaten Musi Rawas - Komiah, Komiah; Suhartono, Suhartono; Gumono, Gumono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this study was to describe the competence of Indonesian language teachers in Indonesian language learning at SMP Negeri Simpang Kosgoro, Muasi Rawas Regency. This research is a quantitative descriptive research. The collection technique uses observation and questionnaires. The data analysis technique was carried out by data reduction, data classification, data interpretation, and conclusions. Wetness test data using membercheck. The results showed that the performance competence of Indonesian civil servant teachers in the National Education Office of Musi Rawas Regency from pegagogical competence, personality competence, social competence, and professional competence, especially in SMP Negeri Simpang Kosgoro showed that it had reached a value range of 75-100 with value 4 in the very good category.